The Impact Of Real Economic Growth On The Unemployment rate (Okun’s law) In Algeria An Econometric Study For The Period (1990-2016) - Sebti, Latifa (Jordan Journal of Economic Sciences, 2019)
This study aims mainly at investigating the impact of the foreign direct investment, inflation rate and the real gross domestic product on unemployment rate in Algeria over the period from 1990 to 2016. In order to achieve these objectives an econometric model that has been designed based on the economic theories and the published researches. The results of the econometric analysis showed the existence of a significant negative impact of both RGDP and FDI on the unemployment rate, the existence of a significant positive impact of the inflation rate on the unemployment rate. In light of the reached results, the study recommended the necessity of Algerian governmnent tendance toward more foreign direct investment policies due to its positive impact in reducing unemployment rates, as well as the working to improve real economic growth rates that reduce unemployment rates to achieve the expectations of the Okun’s Law (0.5), also reducing the inflation rate and conserve it in its minimum values which are not harmful for the domestic economy